The Influence of Work Experience Mediated by Self-Efficacy on the Supervisor Performance in the Hajj and Umrah Guidance Group (KBIHU) Bina Umat Mulya Abadi in Yogyakarta - Yudin, M. Cahya; Wahyuni, Purbudi (CV. Strata Persada Academia, 2025)
This study investigates the influence of work experience on supervisor performance, with self-efficacy acting as a mediating variable, within the context of the Hajj and Umrah Guidance Group (KBIHU) Bina Umat Mulya Abadi in Yogyakarta. Grounded in the Resource-Based View (RBV) theory, which emphasizes human resources as strategic organizational assets, this research addresses the performance variability among pilgrimage supervisors—a phenomenon presumed to be shaped not only by accumulated experience but also by psychological factors such as self-efficacy. Employing a quantitative associative approach, data were collected through structured interviews and standardized questionnaires administered to KBIHU supervisors. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the proposed relationships. The results demonstrate that work experience significantly and positively affects supervisor performance, both directly and indirectly through self-efficacy. These findings underscore the importance of integrating experiential learning with psychological capacity-building in religious non-profit institutions. The study contributes to the theoretical enrichment of human resource management in faith-based service organizations and offers practical implications for the development of targeted training and mentorship programs aimed at enhancing supervisor competence and service quality.